Pre- and In-Service Teachers’ Attitudes Toward Students With Learning Difficulties and Challenging Behavior - Krischler, Mireille; Pit-ten Cate, Ineke M. (Frontiers in Psychology, 2019)
The implementation of inclusive policies is largely dependent on teachers´ willingness to accommodate students with special educational needs (SEN) in mainstream classrooms, which is affected by their perceived competence and attitudes. This study investigated attitudes of pre- and in-service teachers toward students with two types of SEN: challenging behavior and learning difficulties. The three components of attitude (affective, cognitive, and behavioral) were assessed using indirect and direct measures. Results revealed that teachers held negative implicit attitudes toward challenging behavior and learning difficulties, however implicit attitudes did not vary as a function of the type of SEN. Ratings of the stereotypical dimensions warmth and competence and overall ratings of scholastic achievement were affected by professional status and type of SEN. Professional status, implicit attitudes and stereotypical knowledge together explained 52 and 43% of the variance in teachers´ ratings of academic proficiency for students with challenging behavior and learning difficulties, respectively. Results are interpreted within the theoretical framework and implications for teacher training are discussed.